An Enduring or Dying Peasantry? Interactive Impact of Famine and HIV/AIDS in Rural Malawi - Bryceson, Deborah Fahy; Fonseca, Jodie (International Food Policy Research Institute, 2006)
This chapter concentrates on the material conditions and attitudinal perspectives of local villagers, drawing primarily on transcripts of key informant interviews and focus group discussions from three villages to examine the interactions between HIV/AIDS and famine in rural Malawi. Our investigations were part of a CARE International/RENEWAL study carried out between December 2003 and March 2004 in Lilongwe rural district, Central Region.1 The chapter focuses on the response of Malawian peasant farmers to the combined threats of famine and HIV/AIDS and quotes extensively from our interviews and discussions in order to convey how rural peasant farmers perceive the challenges they face. The first section provides background on rural livelihoods in Malawi and various historical influences shaping the peasantry over time, followed by a consideration of changing famine coping strategies.